1986
DOI: 10.1677/joe.0.1100293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen ion concentration on aldosterone secretion by isolated perfused canine adrenal glands

Abstract: The direct effects of changes in extracellular hydrogen ion (H+) concentration on aldosterone secretion under basal, angiotensin II- and potassium-stimulated conditions were studied in isolated, perfused canine adrenal glands. Changes in extracellular H+ concentration were induced by altering either the partial pressure of CO2 (pCO2) or the HCO3- concentration of the perfusate. Acid-base disturbances had a more pronounced effect on aldosterone secretion under stimulated than under basal conditions. Increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A decrease in pH i in glomerulosa cells occurs in response to extracellular acidification, and alterations of pH i have been implicated in the stimulation of aldosterone secretion by AngII and K + (Horiuchi et al 1989, Conlin et al 1990 -induced Ca 2+ release, and diacylglycerol-induced association of protein kinase C with plasma membrane in other cell types (Albuquerque & Leffler 1998, Hulme & Orchard 1998, Nishino et al 1998 Peng et al 1998, Wu & Fry 1998, Kourie 1999 (Schneider & Kramer 1986, Wang et al 1992 and [Na + ] o (Saruta et al 1972, Lobo et al 1978, that influence aldosterone secretion through Ca 2+ -dependent mechanisms. Indeed, results of the present studies confirm previous reports (Chiu & Freer 1978, Radke et al 1986b, Raff & Jankowski 1993 (Chiu & Freer 1978). In the present studies, only the secretory response to AngII was increased, albeit by a smaller reduction of pH o (from 7·4 to 7·0).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A decrease in pH i in glomerulosa cells occurs in response to extracellular acidification, and alterations of pH i have been implicated in the stimulation of aldosterone secretion by AngII and K + (Horiuchi et al 1989, Conlin et al 1990 -induced Ca 2+ release, and diacylglycerol-induced association of protein kinase C with plasma membrane in other cell types (Albuquerque & Leffler 1998, Hulme & Orchard 1998, Nishino et al 1998 Peng et al 1998, Wu & Fry 1998, Kourie 1999 (Schneider & Kramer 1986, Wang et al 1992 and [Na + ] o (Saruta et al 1972, Lobo et al 1978, that influence aldosterone secretion through Ca 2+ -dependent mechanisms. Indeed, results of the present studies confirm previous reports (Chiu & Freer 1978, Radke et al 1986b, Raff & Jankowski 1993 (Chiu & Freer 1978). In the present studies, only the secretory response to AngII was increased, albeit by a smaller reduction of pH o (from 7·4 to 7·0).…”
Section: Discussionsupporting
confidence: 92%
“…Further, an effect of H + to increase the transfer of cholesterol to mitochondria, with or without a concomitant effect to increase its translocation from the outer to the inner membrane, could account for the greater Ca 2+ sensitivity of AngII-stimulated aldosterone secretion. Jefcoate & Boyd (1971) presented evidence that H + directly stimulated cholesterol side-chain cleavage in isolated bovine adrenocortical mitochondria, and Radke et al (1986b) suggested that H + increased the conversion of corticosterone to aldosterone by perfused canine adrenals. However, neither the rate of pregnenolone production from endogenous cholesterol nor the rate of aldosterone production from exogenous corticosterone was affected by reduction of pH o from 7·2 to 6·8 (Raff & Jankowski 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, kidney epithelial cells make and secrete ET-1 31 and might also be a source of the augmented kidney ET-1. In addition, increasing perfusate acidity augments Aldo secretion from isolated perfused adrenal glands, 32 and H þ -inducing dietary protein 23,33 and NH 4 Cl 34 increase plasma Aldo in rats and humans, respectively. Additional studies will be necessary to determine precisely how H þ retention associated with reduced GFR increases kidney AII, ET-1, and Aldo levels.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro studies show that an acid extracellular environment increases ET release from human glomerular endothelial cells (33) and that a more acid perfusate increases aldosterone release from isolated, perfused adrenal glands (23). Consequently, CKD 2 subjects appear to be able to sense an aspect of retained H ϩ .…”
Section: Discussionmentioning
confidence: 99%